2023
DOI: 10.3389/fpls.2023.1125378
|View full text |Cite
|
Sign up to set email alerts
|

Short-term transcriptomic analysis at organ scale reveals candidate genes involved in low N responses in NUE-contrasting tomato genotypes

Abstract: BackgroundUnderstanding the complex regulatory network underlying plant nitrogen (N) responses associated with high Nitrogen Use Efficiency (NUE) is one of the main challenges for sustainable cropping systems. Nitrate (NO3-), acting as both an N source and a signal molecule, provokes very fast transcriptome reprogramming, allowing plants to adapt to its availability. These changes are genotype- and tissue-specific; thus, the comparison between contrasting genotypes is crucial to uncovering high NUE mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 124 publications
1
4
0
Order By: Relevance
“…Overall, they identified 7,667 and 6,015 unique DEGs in shoot and root, respectively. In this study, they identified a number of DEGs consistent with our study but their results also underlined the importance of considering the kinetic of gene expression (Sunseri et al 2023). One of the hypotheses for our results might be that the long duration of the stress ended homogenising the plant's responses or allowed compensation by other unknown mechanisms.…”
Section: Transcriptome Insight Into N Deficiencysupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, they identified 7,667 and 6,015 unique DEGs in shoot and root, respectively. In this study, they identified a number of DEGs consistent with our study but their results also underlined the importance of considering the kinetic of gene expression (Sunseri et al 2023). One of the hypotheses for our results might be that the long duration of the stress ended homogenising the plant's responses or allowed compensation by other unknown mechanisms.…”
Section: Transcriptome Insight Into N Deficiencysupporting
confidence: 89%
“…The transcriptome response of 35-days plant of the cultivar Moneymaker was assessed when cultivated with a solution containing 4 mM (stress) or 8 mM (control) of nitrogen (Renau-Morata et al, 2021). The other study focused on the short term (8h - 24h) transcriptome response differences in shoot and root between a pair of high-NUE (Regina Ostuni) and low-NUE (UC82) cultivars (Sunseri et al, 2023). The plants were grown for 20 days and then stressed (0.5 mM N) or maintained in controlled conditions (10 mM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Solyc07g008240 was found downregulated which is responsible for scavenging NO [94]. Solyc02g090210 is reported for low nitrogen tolerance [59] and it was downregulated while Solyc03g026040 is involved in tomato response to low nitrogen [42,43] and it was upregulated. Solyc02g076980 reported for resistance to Cladosporium fulvum [40] and Solyc03g095650 involved in plant resistance, such as Ralstonia solanacearum infection in tomato, Pseudomonas syringae infection in Arabidopsis and Phytophthora parasitica infection in tomato [44].…”
Section: Discussionmentioning
confidence: 99%